In situ high temperature X-ray diffraction, transmission electron microscopy and theoretical modeling for the formation of WO3 crystallites1. Issue 36 (28th September 2015) - Pokhrel, Suman; Birkenstock, Johannes; Dianat, Arezoo; Zimmermann, Janina; Schowalter, Marco; Rosenauer, Andreas; Ciacchi, Lucio Colombi; Mädler, L.
<x xml:space="preserve">Abstract</x> The structural transformation of WO3 at high temperatures.